IMPLEMENTASI KEBIJAKAN PENGELOLAAN ARSIP PEMERINTAHAN DESA DALAM GERAKAN NASIONAL SADAR TERTIB ARSIP DI DESA CIKERUH - Kasman, Andi; Destrian, Ope; Herdiansah, Ari Ganjar; Sudarma, Sudarma; Rayhani, Fahira Salima (Universitas Padjadjaran, 2025)
The implementation of village government archive management policies is the backbone of good governance at the local level. This article aims to analyze the implementation of archive management policies in the Cikeruh Village Government in support of the National Movement for Awareness of Archive Order (GNSTA). GNSTA encourages institutional awareness, including village governments, to create orderly policies, organizational order, human resource (HR) order, infrastructure order, and archive management order. A descriptive qualitative approach is used to review village archive policies, particularly in terms of the implementation of Official Document Arrangements (TND), Archive Classification (KA), Dynamic Archive Security and Access Classification System (SKKAD), and Archive Retention Schedule (JRA). The results of the study indicate that Cikeruh Village needs to strengthen the legitimacy of internal policies through Village Head Regulations (Perkades) and increase human resource capacity so that archive management can function as an accountability tool and facilitate public services. The implementation of the state archives management policy at the Cikeruh Village government level, Sumedang Regency, demonstrates important points that can increase village officials' awareness of state archives' continuing secondary value as a collective memory of the nation that is worthy of being preserved. This is supported by aspects of increasing the capacity of Archival Human Resources with the importance of collaboration for the sustainability of village administration and by aspects of the implementation of the Village Government Archives Management Application to accelerate excellent public services, as the 18th Village SDGs activity. Implementasi kebijakan pengelolaan arsip pemerintahan desa merupakan tulang punggung terwujudnya tata kelola pemerintahan yang baik (good governance) di tingkat lokal. Artikel ini bertujuan untuk menganalisis implementasi kebijakan pengelolaan arsip di Desa Cikeruh dalam mendukung Gerakan Nasional Sadar Tertib Arsip (GNSTA). Mendorong kesadaran institusi pemerintah desa Cikeruh, untuk menciptakan tertib pengelolaan arsip sebagai batasan kajian penelitian. Pendekatan kualitatif deskriptif digunakan untuk menganalisis implementasi kebijakan pengelolaan kearsipan desa, khususnya penerapan Tata Naskah Dinas (TND), Klasifikasi Arsip (KA), Sistem Klasifikasi Keamanan dan Akses Arsip Dinamis (SKKAD), dan Jadwal Retensi Arsip (JRA). Hasil kajian menunjukkan Desa Cikeruh perlu memperkuat legitimasi kebijakan internal melalui Peraturan Kepala Desa (PERKADES), meningkatkan kompetensi kapasitas SDM, dan implementasi aplikasi kearsipan pemerintahan desa, agar pengelolaan arsip dapat berfungsi sebagai alat akuntabilitas dan mempermudah pelayanan publik. Implementasi kebijakan pengelolaan arsip negara di tingkat pemerintah Desa Cikeruh, Kabupaten Sumedang Provinsi Jawa Barat menunjukkan poin penting yang dapat meningkatkan kesadaran perangkat desa terhadap arsip negara yang memiliki nilai sekunder berkelanjutan (continiung value) sebagai memori kolektif bangsa untuk tetap layak dilanjutkan. Didukung pada aspek peningkatan kapasitas SDM Kearsipan dengan pentingnya kolaboratif untuk keberlangsungan administrasi desa dan pada aspek penerapan Aplikasi Pengelolaan Arsip Pemerintah Desa untuk percepatan layanan publik yang prima sebagai kegiatan SDGs Desa ke-18. The implementation of village government archive management policies is the backbone of good governance at the local level. This article aims to analyze the implementation of archive management policies in the Cikeruh Village Government in support of the National Movement for Awareness of Archive Order (GNSTA). GNSTA encourages institutional awareness, including village governments, to create orderly policies, organizational order, human resource (HR) order, infrastructure order, and archive management order. A descriptive qualitative approach is used to review village archive policies, particularly in terms of the implementation of Official Document Arrangements (TND), Archive Classification (KA), Dynamic Archive Security and Access Classification System (SKKAD), and Archive Retention Schedule (JRA). The results of the study indicate that Cikeruh Village needs to strengthen the legitimacy of internal policies through Village Head Regulations (Perkades) and increase human resource capacity so that archive management can function as an accountability tool and facilitate public services. The implementation of the state archives management policy at the Cikeruh Village government level, Sumedang Regency, demonstrates important points that can increase village officials' awareness of state archives' continuing secondary value as a collective memory of the nation that is worthy of being preserved. This is supported by aspects of increasing the capacity of Archival Human Resources with the importance of collaboration for the sustainability of village administration and by aspects of the implementation of the Village Government Archives Management Application to accelerate excellent public services, as the 18th Village SDGs activity.